If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 2i = 4 Add '-4' to each side of the equation. 4 + -4 + 2i = 4 + -4 Combine like terms: 4 + -4 = 0 0 + 2i = 4 + -4 2i = 4 + -4 Combine like terms: 4 + -4 = 0 2i = 0 Solving 2i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Divide each side by '2'. i = 0 Simplifying i = 0
| 12y=1x+b | | -8g=.48 | | 0.6r=.0005 | | -7y=-6.3 | | 2(x+1)=3(x+4)+10 | | 0.6=r+.0005 | | (3x^2-2x^2+2x-5)*x+1= | | x+(-28)=53 | | .3k=-12 | | 14=6-4y | | 3(10x+4)=8(3x+6) | | z^2=z-12 | | 5r=-.15 | | 3x+2(x+2)=5-4x+2 | | (2x-5)/6-(3x-2)/3=(2x-5)/2 | | .0005=0.6r | | 3x+14=7x+2 | | -6x+5=77+2x | | 20y+3=7 | | 5x-7=-7x+29 | | .0005=0.6 | | -2x-10=-7-5x | | 0.75+2(x-0.5)=2p | | 7(5t-1)-18t=12t-(3-t) | | x^2+4x=22 | | -2-2x=3x+3 | | 2(x+5)=70 | | 2u=-1.6 | | 7a+1a= | | -2-2x=3x+17 | | 20x^2-21x-27=0 | | 4(2x+2)+6(x-4)=8 |